Assessment of the Plastic Inputs From the Seine Basin to the Sea Using Statistical and Field Approaches - Tramoy, Romain; Gasperi, Johnny; Dris, Rachid; Colasse, Laurent; Fisson, Cédric; Sananes, Sarah; Rocher, Vincent; Tassin, Bruno (Frontiers in Marine Science, 2019)
Global estimations state that between 0.5 and 12.7 million metric tons of plastic enter the oceans each year. They are however associated with great uncertainties due to methodological difficulties to accurately quantify land-based plastic fluxes into the oceans. New studies at basin scale are thus needed for better model calibrations. Here, a modelling approach based on Jambeck’s statistical method and a field approach are compared in order to (i) quantify plastic fluxes in the Seine River and (ii) characterize and constrain uncertainties of both approaches. Despite the simplicity of the statistical approach and rough extrapolations, both methods yield similar results, i.e. between 1,100 and 5,900 t/yr of plastic litter flowing into the Seaof which about 88–128 t/yr are removed by cleaning operations. According to the Marine Strategy Framework Directive (2008/56/EC) , actions are required to quantify plastic fluxes entering the oceans. Among different methods, a better use of the data from the waste collection should be considered. The development of a national and homogenous platform listing all the collects would be a first step in that direction.